Morphological features of the soil cover of slope lands in the south of the Volga uplands within the urban landscapes of Volgograd - O. A. Gordienko; E. A. Ivantsova (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
The paper deals with morphological properties of agrogenically transformed chestnut soils of slope lands in the south of the Volga upland within the urban landscape of Volgograd. It is established that as a result of agrogenesis, erosion, land use change, as well as of agroforestry reclamation measures performed, both anthropogenic deeply transformed and postagrogenic soils have been formed. The greatest changes under the influence of agrogenesis are noted in morphological structure of profiles. Agrogenesis results in degradation of soils involved in active agricultural use due to intensified sheet and rill erosion. In eroded soils there is noticed a decrease in the thickness of agrohumic layer, formation of furrow bottom compaction and changes in structure. Their characteristic feature is the presence on the surface of a homogeneous agro-abraded horizon with lumpy structure, in the lower part of which secondary carbonates inherited from the carbonate horizon and resulted from deep plowing may occur. Soils slightly exposed and not exposed to erosion processes have an agrohumus horizon on the surface, which depending on soil tillage can have thickness from 19 to 36 cm. At present, the annual agricultural practices at the plot include mowing of weeds and disk plowing to 20 cm depth. Earlier moldboard plowing to 40 cm depth was performed. All agrogenically-modified soils are characterized by HCl reaction with carbonates from the surface. Carbonate accumulations in agrogenic soils, as a rule, have a segregated form that indicates rapid summer drying of the profile and short period of soil solutions migration. Upper boundary of accumulative-carbonate horizons of agrogenic soils on the average is at 42 cm depth. Such occurrence of carbonate horizons in general is typical both of natural non-eroded soils of dry-steppe zone and of soils involved in agricultural land use. Under forest plantations the original chestnut soils were transformed into turbated agrozems due to deep ameliorative cultivation preceded planting of woody and shrub vegetation. Soil preparation practices applied before tree species planting resulted in transformation of original chestnut soils into turbated agrozems, which is due to deep (up to 60 cm) soil reclamation. The forest belt, being a “barrier” between the field parts, contributed to the formation of a stratified small horizon (trait) of 10 cm thickness for more than 70 years due to the constant inflow of fine-grained soil and decay of leaf and herbaceous debris.